Effects of bone-quality configuration, effective peri-implant interface stiffness, and loading configuration on stress distribution in an ultrashort implant system: a three-dimensional finite element analysis - Betül Sümeyra Akça; Sercan Küçükkurt (BMC Oral Health, 2026)
Abstract Background Ultrashort implants may reduce vertical augmentation needs when residual bone height is limited, but reduced intraosseous support may increase sensitivity to eccentric loading. This full-factorial study evaluated the effects of bone-quality configuration, effective peri-implant interface stiffness, and loading configuration in a restored ultrashort implant. Methods A three-dimensional linear static finite element model included a 4.1 × 4.0-mm tissue-level implant, separate abutment and connection screw, and a 7-mm-high molar crown. Four bone-quality configurations (D1–D4), four nominal effective interface-stiffness levels (25%, 50%, 75%, and 100% of adjacent host-bone modulus), and two static 100-N loading configurations—axial (0°) and oblique (30°)—yielded 32 simulations. Stiffness levels were computational surrogates produced by scaling the peri-implant transition-region modulus with tied contacts, not histological osseointegration percentages or healing stages. Component von Mises stress and bone maximum and minimum principal stresses were evaluated. The D1 model at 25% stiffness under the oblique-loading configuration underwent mesh-sensitivity testing at 0.4, 0.3, 0.2, and 0.1 mm. Results At 100% nominal effective interface stiffness, maximum component von Mises stresses under the oblique-loading configuration were 6.9–9.4 times the axial values. Increasing nominal effective interface stiffness from 25% to 100% reduced maximum implant stress by 4.9%–36.0% and 17.2%–42.0% under the axial- and oblique-loading configurations, respectively, with the largest reduction in D4; abutment and crown stresses changed minimally. In D2–D4, increasing nominal effective interface stiffness decreased cortical maximum principal stress and the magnitude of trabecular minimum principal stress but increased the magnitude of cortical minimum principal stress, indicating redistribution. Final refinement changed implant von Mises and cortical maximum principal stresses by 2.31% and 2.75%, below the 3% threshold. Conclusions Loading configuration affected component stresses more than nominal effective interface-stiffness scaling. Within this model, increasing nominal effective interface stiffness reduced implant stress, particularly in lower-support configurations, but component stresses remained higher under the oblique-loading configuration. These comparative trends derive from static, linear-elastic, tied-contact simulations without experimental validation and do not define clinical loading protocols, healing periods, survival probabilities, or failure thresholds.